Large mammals generate both top-down effects and extended trophic cascades on floral-visitor assemblages. (11th June 2019) - Louthan, Allison; Valencia, Emily; Martins, Dino J.; Guy, Travis; Goheen, Jacob; Palmer, Todd; Doak, Daniel
Abstract: Cascading effects of high trophic levels onto lower trophic levels have been documented in many ecosystems. Some studies also show evidence of extended trophic cascades, in which guilds dependent on lower trophic levels, but uninvolved in the trophic cascade themselves, are affected by the trophic cascade due to their dependence on lower trophic levels. Top-down effects of large mammals on plants could lead to a variety of extended trophic cascades on the many guilds dependent on plants, such as pollinators. In this study, floral-visitor and floral abundances and assemblages were quantified within a series of 1-ha manipulations of large-mammalian herbivore density in an African savanna. Top-down effects of large mammals on the composition of flowers available for floral visitors are first shown, using regressions of herbivore activity on metrics of floral and floral-visitor assemblages. An extended trophic cascade is also shown: the floral assemblage further altered the assemblage of floral visitors, according to a variety of approaches, including a structural equation modelling approach (model with an extended trophic cascade was supported over a model without, AICc weight = 0.984). Our study provides support for extended trophic cascades affecting floral visitors, suggesting that trophic cascades can have impacts throughout entire communities.